Identification of Norway Spruce MYB-bHLH-WDR Transcription Factor Complex Members Linked to Regulation of the Flavonoid Pathway - Nemesio-Gorriz, Miguel; Blair, Peter B.; Dalman, Kerstin; Hammerbacher, Almuth; Arnerup, Jenny; Stenlid, Jan; Mukhtar, Shahid M.; Elfstrand, Malin (Frontiers in Plant Science, 2017)
Transcription factors forming MYB-bHLH-WDR complexes are known to regulate the biosynthesis of specialized metabolites in angiosperms through an intricate network. These Specialized metabolites participate in a wide range of biological processes including plant growth, development, reproduction as well as in plant immunity. Studying the regulation of their biosynthesis is thus essential. While MYB transcription factors have been previously shown to control specialized metabolism in gymnosperms, the identity of their partners, in particular bHLH or WDR members, has not yet been revealed. To gain knowledge about MYB-bHLH-WDR transcription factor complexes in gymnosperms and their regulation of specialized metabolism, we identified two bHLH homologs of AtTT8, six homologs of the MYB transcription factor AtTT2 and one WDR ortholog of AtTTG1 in Norway spruce. We investigated the expression levels of these genes in diverse tissues and upon treatments with various stimuli including methyl-salicylate, methyl-jasmonate, wounding or fungal inoculation. In addition, we also identified protein-protein interactions among different homologs of MYB, bHLH and WDR. Finally, we generated transgenic spruce cell lines overexpressing four of the Norway spruce AtTT2 homologs and observed differential regulation of genes in the flavonoid pathway and flavonoid contents.